Effect of A-site and B-site ion replaced with small ions on the intermediate phase in PbZrO3 ceramic - Sukkha, Usa; Vittayakorn, Wanwilai; Muanghlua, Rangson; Niemcharoen, Surasak; Vittayakorn, Naratip (My University, 2014)
The solid solution of (1 - x)PbZrO3-xNaNbO3 ceramics, where x = 0.0-0.08, was synthesized by solid state reaction. The basic characterizations were performed using X-ray diffraction (XRD), dielectric spectroscopy, hysteresis measurement and differential scanning calorimetry (DSC) techniques. The results indicated that the crystal structure of the solid solution, (1 - x)PZ-xNN, where x = 0.00-0.08, is of orthorhombic symmetry. It was found that the effect of NN being replaced with small ions at the A-site and B-site can induce an AFE-like phase in PZ. The FE intermediate phase of PZ cannot be induced, although Zr4+ ions were substituted by small Nb5+ ions. This is due to the decreasing average rate of radii in the A-site (0.1 Å mol-1) being higher than that in the B-site (0.08 Å mol-1). © 2013 Elsevier B.V. All rights reserved.
Keywords: Dielectric properties; Electronic characterisation; Ferroelectricity; Phase transitions